PERAN MEDIASI IMPLEMENTASI SAP BERBASIS AKRUAL TERHADAP EFEKTIFITAS IKLIM KOMUNIKASI DAN KINERJA SIPKD - Asrini, Asrini; Musnaini, Musnaini; Wita Juwita Ermawati; Khaira Amalia Fachrudin; Juanda, Juanda; Conchita Valentina Latupapua (Develop, 2024)
This study aims to explain the role of accrual-based SAP implementation in mediating the influence of communication climate antecedents that affect the performance of regional financial management information systems directly and indirectly. the research approach uses quantitative, with random sampling techniques distributing 100 questionnaires to employees of the planning and finance sections in 10 Jambi Regional Government Organizations. data analysis Path Least Square with SMARTPLS software. the results of these findings indicate that the climate directly affects SIPKD Performance unaccepted, while indirectly accepted full mediation. This shows that the role of mediation is key to SIPKD performance in local government. further research can develop hypotheses on the simultaneous influence of the communication climate and the implementation of accrual-based SAP on SIPKD performance.